Secondary research information sources and methods. - Stewart, David W. (Applied social research methods series, 1993)
'Secondary Research' has been revised to give the latest information on computer-based storage and retrieval systems. The second edition features expanded coverage of computer-based information, including a new chapter on CD-ROM products and updated coverage of on-line information search services.